Web performance playbook. (O'Reilly Media, Inc., 2018)
The web today is as competitive an environment as any that a business will face. Whether yoursis a retail site, a news and information site, or whatever it might be, getting and keeping visitorsthere is a tougher challenge than ever, especially with so many competing sites just a click ortap away. And nothing will send your visitors heading for another site faster than a slow-loadingpage, or animations that grind to a halt and freeze the page on your users. Web performance is important. Not only can it help increase the loyalty of your visitors, it canhelp you achieve higher rankings in search results. To stay ahead of the competition, whetheryou're a web designer or developer you need to be well versed in the terminology and basicskills that underpin web performance technology to ensure that your sites respond as expected,with no lag time apparent to your visitors. In this screencast, expert Eli Fitch takes you on a hands-on, introductory exploration of theimpact that web performance--good and bad--can have on you and your users. In this series ofshort, easy-to- absorb videos, Eli introduces you to the major topics that define web performanceso that you can determine where to start and see how web performance can improve your apps.You'll look at methods to improve web performance, from image optimization and codeminification, to lazy loading and SVG icons. You'll also investigate techniques like front loadingand how to optimize animation performance. If you are an entry- to intermediate-level webdeveloper, you need to spend a little time with Eli and let him show you how improve yourwebsite's performance. What you'll learn--and how you can apply it. Image optimization, front loading, animation performance, and much more Understand critical rendering, script loading, and code minification How to use lazy loading, loading indicators, and SVG icons This screencast is for you because... You understand web performance is important, but need an overview of what's involved You need to understand how to frame the importance of web performance for other people in your company You're interested in taking on performance tasks, but need to know about the various other parts You're a front end developer or designer and you want to advance your skills in important, but non-core, areas Prerequisites You should have knowledge of CSS and HTML You should be familiar with SVG.